Identification of new religious movements in R. Stark’s research programme - Martinovich, Vladimir A. (Journal of the Belarusian State University. Sociology, 2023)
This article is devoted to the problem of identification of new religious movements in the research programme of the famous American sociologist of religion Rodney Stark. The author describes in general terms the legacy, contribution of the scientist to the development of the sociology of religion and the methodological shifts he made towards the analysis of religious organisations, also adjusted for a diachronic perspective. Particular attention is paid to the presentation of theoretical and methodological foundations of R. Stark’s typology of religious organisations, as well as his concept of tension with society. Based on the results of the author’s research, the problematic points proposed by R. Stark are identified, both in the methodology of analysis and in the theory of the system of relations between religious organisations and society. Specific theoretical and methodological proposals are made to resolve the revealed problems, including those based on the study of the social identification of religious organisations.
Keywords: sociology of religion; social identification; new religious movements; religion and society; church; rejection of society; tension with society